Valid representation of a highly dynamic collision avoidance scenario in a driving simulator. (May 2015) - Zöller, Ilka; Betz, Alexander; Mautes, Nicole; Scholz, Lucas; Abendroth, Bettina; Bruder, Ralph; Winner, Hermann
Highlights: No behavior validity in a static driving simulator for a high dynamic scenario. Different behavior of the participants is caused by the missing vestibular feedback. Calculating the needed workspace to perform this dynamic scenario. Today's systems are not capable performing the introduced test maneuver. Abstract: In Germany the second-most frequent accidents in road traffic are rear-end collisions. For this reason rear-end collisions are quite important for accident research and the development of driving safety systems. To examine the functionality and to design the human–machine-interface of new driving safety systems, especially in the early development phase, subject tests are necessary. Because of the great hazard potential of such safety critical scenarios for the test persons, they are often conducted in a driving simulator (DS). Accordingly, validity is an important qualification to ensure that the findings collected in a simulated test environment can be directly transferred to the real world. This paper regards the question of driving behavior validity of DS in critical situations. There are hardly any validation studies which analyze the driving behavior in a specific collision avoidance situation. The validation study described in this paper aims to evaluate the behavioral validity of a fixed-base simulator in a collision avoidance situation. For this reason a field study from 2007 was replicated in a fixed-base simulator environment. The main questions of this validation study were if the driver can notice an active hazard braking system and if the driving behavior in a static simulator can be valid in such a critical situation. The key finding of the study states that there is no driving behavior validity in a static driving simulator for the tested dynamic scenario. The missing vestibular feedback causes a different behavior of the participants in field and simulator. The resulting absence of comparability leads to non-valid performance indicators. But these indicators are key parameters for analyzing the function and acceptance of active braking systems. So the question arises, which motion performance does a motion base have to provide in order to achieve valid acceleration simulation of such a highly dynamic collision avoidance scenario. The DS's performance is measured in workspace, velocity and acceleration.